The correlation of power and opposition between intellectual dialectics and determinants of rational organization - Abdulmahdi, Assistant. Lecturer Hasan Falah (The International and Political Journal, 2023)
The most ancient societies are witnessing political phenomena that are attracted to two main axes: authority and opposition, to form an authentic social-political entity inseparable from human thought. Although the presence of political authority is necessary to lift society out of a state of chaos, organize its relations, impose the law, and invest its energies in an optimal manner, it does not hide the disparity in privileges between those holding power and those subject to it. This situation stimulates arbitrary mechanisms that tempt the ruling elites to cling to power. At the same time, it opens the justificatory and necessary space for the emergence and nourishment of opposition as a social reaction to control the course of the political situation. This is in addition to ensuring its stability outcomes in accordance with individual and collective interests as an actor that cannot be ignored or dispensed with, considering the dynamics and determinants of mutual influence between the authority and the opposition to maintain the sustainability and continued legitimacy of the political system.